Survival with nonmelanoma skin cancer in Germany3. (22nd March 2016) - Eisemann, N.; Jansen, L.; Castro, F.A.; Chen, T.; Eberle, A.; Nennecke, A.; Zeissig, S.R.; Brenner, H.; Katalinic, A.; ,
Summary: Background: Nonmelanoma skin cancer (NMSC) is the most common cancer in Germany, but detailed information on survival is lacking. Objectives: To provide survival estimates for female and male patients with basal cell carcinoma (BCC), squamous cell carcinoma (SCC), sarcoma, adenocarcinoma and Merkel cell carcinoma. Further subgroup analyses were carried out by age, tumour stage and body site. Methods: In total 459 640 patients diagnosed with NMSC in 1997–2011 were included from population‐based cancer registers, covering a population of 33 million inhabitants. Age‐standardized absolute and relative 5‐year and 10‐year survival were calculated using period analysis. Results: The absolute and relative 5‐year survival were 87·1% and 102·9% for BCC, 77·6% and 93·6% for SCC, 82·1% and 96·0% for sarcoma, 71·4% and 85·7% for adenocarcinoma and 60·0% and 70·7% for Merkel cell carcinoma, respectively. Higher age, female sex and advanced stage were associated with lower survival. Conclusions: A comprehensive overview of NMSC survival in Germany is provided. The differences between the NMSC subtypes require a more differentiated consideration of patient survival. The survival advantage of patients with BCC may be related to health‐promoting factors related to the BCC diagnosis, such as changes to a healthier lifestyle. Abstract : What's already known about this topic? The overall survival of patients with nonmelanoma skin cancer is very good. What does this study add? We provide a comprehensive overview of absolute and relative survival by histological subgroup, sex, age group, stage and body site. Patients with basal cell cancer have a better survival than the general population, while survival with other histological subtypes is worse, especially Merkel cell carcinoma. Higher age, female sex and advanced stage were associated with lower survival. Linked Comment: Baade. Br J Dermatol 2016;174: 713–714 . Plain language summary available online